2019
DOI: 10.18203/2320-6012.ijrms20191623
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of troponin-I level with left ventricular systolic dysfunction after first attack of non-ST segment elevation myocardial infarction

Abstract: Background: Coronary Heart Disease (CHD) is the most common category of the heart disease and is found to be the single most important cause that leads to premature death in the developed world. Recognizing a patient with ACS is important because the diagnosis triggers both triage and management. cTnI is 100% tissue-specific for the myocardium and it has shown itself as a very sensitive and specific marker for AMI. Ventricular function is the best predictor of death after an ACS. It serves as a marker of myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In this study, cardiac complication was also observed consequence of NaF administration as recorded by higher expressions of cardiac troponin I (CTnI). CTnI has been used clinically as diagnostic marker for various cardiovascular dysfunction . It is worth to note that Luteolin co‐administration lowered the expressions of CTnI in comparison to the control and NaF alone treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cardiac complication was also observed consequence of NaF administration as recorded by higher expressions of cardiac troponin I (CTnI). CTnI has been used clinically as diagnostic marker for various cardiovascular dysfunction . It is worth to note that Luteolin co‐administration lowered the expressions of CTnI in comparison to the control and NaF alone treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that the LVEF had a negative correlation with troponin I levels (r= -0.54, P = 0.001). Despite the above fact, there was an exploration of troponin T, whereby it was also revealed that there was a negative correlation between troponin T levels and LVEF (r= -0.72, P = < .0001) [15,16,17]. In our findings, we showed that there was a significant negative relationship between troponin I and left ventricular ejection fraction in patients with OCAD and CMVD (r= -0.311, P = 0.04).…”
Section: Discussionmentioning
confidence: 47%
“…All these findings replicated the findings of Khan and his colleagues who did a same study on patients of NSTEMI. 13 Like some other studies, there was a significant negative correlation between LVEF and troponin I. 19…”
Section: Discussionmentioning
confidence: 65%
“…Mean age of all patients was 58.86±13.44 years which was similar studies conducted in Bangladeshi population. 12,13 Most of the patients in this study were male.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation